2016
DOI: 10.15763/issn.2470-9670.2016.v1.i1.a4
|View full text |Cite
|
Sign up to set email alerts
|

Signage as Marketing Communication

Abstract: Further advancement of the growing knowledge base in the emerging, cross-disciplinary field of signage should benefit from investigation into how and why communication effects of signs occur, as such insights could potentially inform evidence-based decision-making. To facilitate such research, the authors propose a conceptual model of signage as a marketing communication tool. Model components include objective and subjective traits of signs, characteristics and states of viewers, contextual variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Signs are used to identify and advertise a business, as well as its location to potential customers (Kuhn et al, 1997). Signs also help to attract customers, communicate information about the store's image and atmosphere and serve to distinguish a business from its competitors (Berman and Evans, 2007;Kellaris and Machleit, 2016). For very small businesses, signage is often the most important means of communicating with potential customers and the most effective and affordable means of advertising (Morris, 2001;Kelly, 2010;Taylor et al, 2012).…”
Section: Design Standards and Sign Regulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Signs are used to identify and advertise a business, as well as its location to potential customers (Kuhn et al, 1997). Signs also help to attract customers, communicate information about the store's image and atmosphere and serve to distinguish a business from its competitors (Berman and Evans, 2007;Kellaris and Machleit, 2016). For very small businesses, signage is often the most important means of communicating with potential customers and the most effective and affordable means of advertising (Morris, 2001;Kelly, 2010;Taylor et al, 2012).…”
Section: Design Standards and Sign Regulationsmentioning
confidence: 99%
“…This is due to the fact that aspects of size, illumination, contrast and location all combine to influence the visibility of a sign and thus its effectiveness as a communication devise (Hawkins, 2011;Jourdan et al, 2013;Auffrey and Hildebrandt, 2017). Thus planners and communities need to have an awareness and understanding of how aspects of sign design and placement can impact the ability of signs to communicate and serve as an effective marketing tool for businesses (Kellaris and Machleit, 2016).…”
Section: Design Standards and Sign Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on research demonstrating the importance of context, Kellaris and Machleit (2016) propose a conceptual model of signage as a marketing communication tool. Their model seeks to provide a framework for pulling together decades of signage research into a "big picture" so that "missing pieces of the puzzle" might be identified and pursued (10).…”
Section: Introductionmentioning
confidence: 99%
“…Also, such findings could raise questions about OPS design and location practices, and the impact of local sign regulations on OPS effectiveness. It is in this sense that this research intends to identify one of the missing pieces of the signage research puzzle noted by Kellaris and Machleit (2016).…”
Section: Introductionmentioning
confidence: 99%